Development of Audit Working Papers and Maturity Levels for Helpdesk Information Technology Governance Using COBIT 2019 in the DSS Domain: (A Case Study of XYZ University) - Syifa'ul Aini Zahroh; Renny Sari Dewi; Rindu Puspita Wibawa (Universitas Negeri Surabaya, 2025)
The implementation of the helpdesk information system at University XZY in Surabaya plays a crucial role in supporting the management of complaints from students and academic staff. However, several issues have been identified, including inadequate user data verification mechanisms, potential privacy violations due to open access to complaint reports by other users, and the absence of a structured incident resolution report. These challenges impact the performance and integrity of the information system. To address these problems, this study aims to design an audit working paper using the COBIT 2019 framework, specifically focusing on DSS02 (Managed Service Requests and Incidents), DSS03 (Managed Problems), and DSS04 (Managed Continuity) to evaluate and improve the system. The findings indicate that all three domains are at capability level 3 (Defined), which implies that processes are documented but not yet measured consistently. This study produces an audit working paper, improvement recommendations, and an implementation cost estimation, which can serve as a strategic reference for university XYZ in enhancing the quality, security, and sustainability of its helpdesk system.